The Awakening of Muslim Democracy - Jay Willoughby (International Institute of Islamic Thought, 2015)
Jocelyn Cesari (senior fellow at Georgetown University’s Berkly Center; director, Islam in World Politics program), teaches contemporary Islam at the Harvard Divinity School and directs its Gerogetown-based interfaculty “Islam in the West” program. On March 3 at the IIIT headquarters in Herndon, VA, she elaborated on the topics discussed in her latest book: The Awakening of Muslim Democracy: Religion, Modernity, and the State (Cambridge University Press: 2014). She explained that this book was based on three years of research on state-Islam relations in Egypt, Turkey, Iraq, Pakistan, and Tunisia. She began her talk by saying that she was interested in “broadening out the concept of political Islam,” which had existed before the now well-known movements and parties in the Muslim world. The key moment in this regard was the building of nation-states in Turkey, Egypt, Tunisia, Iraq (under Saddam Hussein), and Pakistan. She pointed out how the West was enthusiastic about Arab Spring, which brought both men and women into the streets without signs proclaiming “Islam” in a “bizarre” manner of protest. She maintained that political Islam cannot be limited only to secularism and the state, for the former, especially in Europe, is supposed to engender the decline of religiosity, the movement of religion to the private sphere, and the separation of religion and state. But all of this is unique to the West because India, the oft-proclaimed world’s “largest democracy,” is officially secular despite its pervasive Hinduism. She wondered why the West cannot see Islam in the same way. And, moreover, why does the last century of the very western approaches of secularization and modernization have to determine what ...